THE EFFECT OF COUNTERPRESSURE THERAPY AND LAVENDER AROMATHERAPY ON REDUCING PAIN INTENSITY IN THE FIRST STAGE OF LABOR - Veryudha Eka Prameswari; Indra Yulianti (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
First stage labor pain is a physiological process that can cause physical and psychological stress for mothers giving birth, so it requires effective and safe non-pharmacological treatment. Objective: This study aims to determine the effect of a combination of counterpressure therapy and lavender aromatherapy on reducing the intensity of first stage labor pain. Method: This type of study used a quasi-experimental design with a one group pre-test and post-test design approach. Sampling was carried out using an accidental sampling technique with a total of 25 mothers giving birth in the first stage. Measurement of pain intensity used a Visual Analogue Scale (VAS) or Numeric Rating Scale (NRS). Bivariate data analysis used the Wilcoxon Signed Ranks Test. Results: The characteristics of respondents showed that the majority were in a healthy reproductive age of 20–35 years (80%) and were primiparous (60%). Before the intervention, most respondents experienced severe pain (72%) with an average value (mean) of 7.24 ± 1.15. After being given a combination of counterpressure therapy and lavender aromatherapy, pain intensity decreased to moderate pain (52%) and mild pain (44%) with an average value of 4.12 ± 0.98. The results of the Wilcoxon statistical test showed a p-value <0.001 (p <0.05). Conclusion: The combination of counterpressure therapy and lavender aromatherapy had a significant effect on reducing the intensity of pain in the first stage of labor. This combination therapy can be recommended as one of the non-pharmacological independent midwifery care interventions to reduce labor pain.